Direct oral anticoagulants in patients with nonvalvular atrial fibrillation and extreme body weight. (10th August 2021) - Bodega, Francesca; Russi, Anita; Melillo, Francesco; Blunda, Fabiana; Rubino, Claudia; Leo, Giulio; Cappelletti, Alberto; Mazzone, Patrizio; Mattiello, Paolo; Della Bella, Paolo; Castiglioni, Alessandro; Alfieri, Ottavio; et al.
Abstract: Background: Limited clinical data exist describing the use of direct oral anticoagulants (DOACs) in patient with extreme body weight. Thus, the International Society of Thrombosis and Haemostasis (ISTH) recommends avoiding DOACs in patients with weight >120 Kg, and on the contrary, no restrictions exist for underweight patients. Objective: To evaluate the effects of extreme body weight on DOAC activity and to compare the clinical outcomes of patients with an extreme body weight versus patients with a normal weight (61‐119 Kg) treated with DOACs. Methods: Single tertiary care Italian centre multidisciplinary registry including nonvalvular atrial fibrillation (NVAF) patients treated with DOACs. Based on weight, three subcohorts were defined: (i) underweight patients (≤60 Kg); (ii) patients with a normal weight (61‐119 Kg, as control group); and (iii) overweight patients (≥120 Kg). Primary efficacy endpoint was 2‐year rate of thromboembolic events. Primary safety endpoint was 2‐year rate of major bleeding. Event‐free survival curves among groups were compared using Cox‐Mantel test. Results: 812 NVAF patients were included, 108 patients weighed ≤60 Kg (13%, underweight), 688 weighed between 61 and 119 Kg (85%, normal weight), and 16 weighed ≥120 Kg (2%, overweight). In particular, among underweight patients, dabigatran was prescribed in 26% patients, apixaban in 27%, rivaroxaban in 28% and edoxaban in 22% ones. Instead, among overweight patients, 44% were treated with dabigatran, 25% with apixaban, 25% with rivaroxaban and 4% with edoxaban. Underweight patients were older, more frequently women, with lower creatinine clearance and a history of previous strokes, resulting in higher CHA2DS2‐VASc score than in both remaining groups. Up to 2 years, no statistically significant difference was observed between the three groups of weight for thromboembolic events ( P = .765) and for overall bleeding ( P = .125), but a trend towards decreased overall bleeding rates was noticed as weight increased (24.1% vs 16.7% vs 12.5%, respectively). Conclusion: In this tertiary care centre registry, 15% of patients treated with DOACs presented an extreme weight. Compared to patients with a normal weight, no significant rates of thromboembolic events were observed for underweight or overweight patients. A trend towards decreased overall bleeding frequency as weight increased was highlighted up to 2 years. The present results should be considered as preliminary and hypothesis generating.